Nano Clay Additive Effect on Shear Strength of GFRP Joints - Ahmet Erkliğ; Mehmet Veysel Çakır; Ömer Yavuz Bozkurt (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Adhesivelybonding joints are widely used in various industries such as aviation,automotive and marine due to its advantages such as lightness, sealing ability,low cost, corrosion resistance and uniform stress distribution. Increasing thequality and durability of adhesives using various methods is a matter ofinterest both in science and engineering. This study investigates the role ofthe addition of Nano-clay particles to epoxy resin on the shear strength ofsingle lap GFRP bonding joints. For this aim, Nano-silica particles were addedin epoxy resin, 1%, 2%, 3% and 5% by weight. The experimental results obtainedfrom lap shear test showed that the increase in shear strength was about 36, 91and 63% for 1, 2 and 3 wt. respectively.